Marguerite Patten's Post-War Kitchen : Nostalgic Food and Facts From 1945-1954. - Patten, Marguerite (London Hamlyn, 1998)
The late 1940s and early 1950s was a time when people longed to return to good cooking and Marguerite Patten appeared on television showing people how to cook well. This post-war history of cookery includes authentic recipes and extracts from newspapers and public information leaflets of the time.
Include Index and Illustrations
Keywords: Cooking, British